Phenotypic and genomic analysis of the number of oocytes and embryos of the Gir breed - Rocha, Renata de Fátima Bretanha (2023)
Gir Dairy cattle, a zebu breed (Bos primigenius indicus), are predominant in Brazilian herds due to their tolerance to tropical climate conditions and good milk production. Zebu animals are also more efficient in retrieving oocytes and, consequently, in producing embryos in vitro than taurine cattle (Bos primigenius taurus). In this context, our objectives were (i): to obtain genetic parameters for the number of total (TO) and viable oocytes (VO) and the number of embryos (EMBR) of the Gir breed; (ii): to verify the profile of runs of homozygosity (ROH) and inbreeding depression over TO, VO, and EMBR of the Gir breed and identify signatures of selection, genes, and enriched regions between Gir subpopulations sorted by breeding value for these traits; (iii): to identify genomic regions, genes, and biological processes associated with TO, VO, and EMBR in Gir dairy cattle; (iv): to verify the inheritance of genomic regions and genes associated with TO, VO, and EMBR based on a daughter design approach; (v): to identify the parental origin of the alleles, through genomic imprinting, affecting TO, VO, and EMBR of the Dairy Gir. As results, heritability was moderate for TO and VO, and low for EMBR; repeatability estimates were moderate for all traits; genetic correlations were high; and phenotypic correlations ranged from moderate to high among all traits. All these results suggested that the selection of Gir donors for total oocyte production can be done preferably at younger ages, which might lead to an increase in the number of viable oocytes and embryos obtained and hasten genetic progress. The ROH profile indicates ancient inbreeding in this Gir population. General ROH-based inbreeding had a negative effect on the studied traits, which is important to consider when selecting animals for reproduction in order to avoid inbreeding depression events. From GWAS analyses, we have that ARNT, EGR1, HIF1A, AHR and PAX2 genes are good markers for the production of oocytes and embryos in Gir cattle. Results for a daughter design approach indicated that genomic inheritance is similar between families, especially between TO and VO traits, which is consistent with previous results of high genetic correlation between these traits. Also, genomic regions located on BTA7 between 82974837 and 83997563 base pairs proved to be the most common across families, where genes with oocyte maturation and embryo development related-functions were identified. Parental origin analysis results showed complete paternal imprinting effects affecting TO. Our results contribute new knowledge about oocyte and embryo production for Brazilian livestock, highlighting the importance of studying reproductive traits in cattle. Our findings contribute to the genetic improvement of the Gir breed and direct future research into gene expression and/or omics that may address the traits studied in this work. Keywords: Dairy cattle. Family analysis. GWAS. Imprinting. ROH. Signatures of selection